Use of antidepressants in adolescence: a narrative review (Research, Society and Development, 2022)
Introduction: depression is a psychiatric disorder that affects the general population, but has been aggressive in situations where this public is teenagers. Due to exposure to biological and behavioral mutational factors, it is possible that flows of emotional instability may develop, which may lead to the risk of suicide, including the age group in a risk group that needs to be observed and treated with caution, as there are different limitations compared to the disease. in adults. Objective: we seek to understand the need for treatment beyond conventional measures, expanding the possibility of favorable results that can be achieved with pharmacotherapy associated with behavioral psychotherapy. Methodology: Qualitative research based on the content analysis method was used as a guideline. The research consists of a narrative review, which is a category of broad publications suitable for describing and discussing the development or “state of the art” of a given subject, from a theoretical or contextual point of view. Results and discussion: the results of this study reinforce the idea that the signs of mild to moderate depression in adolescents are similar to characteristics and behaviors that are particular to adolescence, which makes it difficult to differentiate and requires a detailed assessment of the symptoms presented. The need for improvements in the care of these young people is essential to obtain a care process that favors a diagnosis free of confusion with behaviors that are peculiar to the age group. Conclusion: Medicines are the main care and treatment strategy for individuals diagnosed with depression, thus, the understanding of this intervention reaches new aspects and proportions of treatment.